2021
DOI: 10.1002/oby.23088
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Monitoring via Digital Health in Weight Loss Interventions: A Systematic Review Among Adults with Overweight or Obesity

Abstract: Objective: Self-monitoring is a core component of behavioral obesity treatment, but it is unknown how digital health has been used for selfmonitoring, what engagement rates are achieved in these interventions, and how self-monitoring and weight loss are related. Methods: This systematic review examined digital self-monitoring in behavioral weight loss interventions among adults with overweight or obesity. Six databases (PubMed, Embase, Scopus, PsycInfo, CINAHL, and ProQuest Dissertations & Theses) were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 87 publications
6
88
0
2
Order By: Relevance
“…However, wearable activity trackers alone may not be sufficient to achieve the expected lifestyle changes [22], so their inclusion in mHealth multicomponent obesity interventions, which appears to be more effective than app interventions alone [23], could be a beneficial strategy to obtain positive results in diet, physical activity, or other health variables [24,25]. In addition, self-monitoring in digital health interventions is associated with greater weight loss [26], so the use of both approaches could produce better weight outcomes. Despite these promising results, the evidence for long-term efficacy is still limited, revealing that more evidence of effectiveness over long follow-up periods is required [27].…”
Section: Mobile Healthmentioning
confidence: 99%
“…However, wearable activity trackers alone may not be sufficient to achieve the expected lifestyle changes [22], so their inclusion in mHealth multicomponent obesity interventions, which appears to be more effective than app interventions alone [23], could be a beneficial strategy to obtain positive results in diet, physical activity, or other health variables [24,25]. In addition, self-monitoring in digital health interventions is associated with greater weight loss [26], so the use of both approaches could produce better weight outcomes. Despite these promising results, the evidence for long-term efficacy is still limited, revealing that more evidence of effectiveness over long follow-up periods is required [27].…”
Section: Mobile Healthmentioning
confidence: 99%
“…Self-monitoring of diet and physical activity provides an effective behaviour change technique for weight management [ 79 ] and is a core component of behavioural obesity treatment [ 80 ]. It has been demonstrated that dietary self-monitoring itself and the frequency of self-monitoring is linked to weight loss [ 81 ]. Furthermore, self-monitoring tends to positively impact weight loss when combined with other self-regulation techniques, such as goal setting and feedback [ 82 , 83 , 84 ].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Furthermore, self-monitoring tends to positively impact weight loss when combined with other self-regulation techniques, such as goal setting and feedback [ 82 , 83 , 84 ]. Engagement rates for self-monitoring diet were higher in digital than in paper-based self-monitoring [ 81 , 85 ].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Many of the traditional commercial weight loss companies (i.e., WW, Jenny Craig, and Nutrisystem), 1 , 12 , 13 as well as newer companies (i.e., Noom), 6 now offer both telehealth and mHealth apps, some of which have been demonstrated to foster behavioral change and promote weight loss. 1 , 6 Although, telehealth and mHealth app‐based approaches to treat obesity are in their infancy, 8 they are quickly evolving and transforming the essential modalities for obesity treatments, including medical nutrition therapy (MNT), 14 self‐monitoring weight loss tools, 15 , 16 promotion of physical activity, 17 , 18 and intensive behavioral therapy (IBT). 19 For example, just‐in‐time adaptive interventions (JITAIs), 20 which utilize technology that dynamically adjusts intervention approaches based on an individuals' changing behaviors in real‐time, have been shown to diminish sedentary behaviors and increase physical activity in individuals with obesity.…”
Section: Telehealth and Mhealth For Obesity Treatmentmentioning
confidence: 99%